(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The article provides an annotated list of rare vascular plants from Lower Dnipro sands (Kherson and Nikolaev oblasts), an annotated list of rare flora includes 126 species (14.3% of the total flora) from 99 genera and 54 families. There are one species from European Red List (Agropyron dasyanthum), two species from Red list of the International Union for Conservation of Nature (Salvinia natans), ten species from the Convention on International Trade in Endangered Species of Wild Fauna and Flora (all representatives family Orchidaceae), seven species from the Convention on the Conservation of European Wildlife and Natural Habitat (Bern) (Ostericum palustre, Lindernia procumbens, Zostera marina - only in Bern), thirty-four species from the Red Book of Ukraine (of which: status "Endangered" have 4 species – Alyssum savranicum, Carex liparicarpos, Fimbristylis bisumbellata, Tephroseris palustris, "Vulnerable" – 23 species, "Rare" – 5 species and "Invaluable" – 6 species), forty-one species from the Red List of the Kherson region, seven species from the Red List of the Mykolaiv region. Forty-two species were proposed for including in the Red List of the Kherson oblast (thirty-nine) and forteen species for Red list of the Mykolayiv oblast (only in RLMO – Centaurea odessana, Centaurium spicatum, Moehringia trinervia). Examining chorology of rarity in the arenas, it was found that Kinburn Spit has highest sozological status seventy-two species, including twenty-nine species of vascular plants, which are nowhere else to be found on the Lower Dnieper sands (Crambe maritima, Eringium maritimum, Astrodaucus littoralis). The second place in terms number of rare species is occupied by the Ivanovska arena - fifty-one species, of which twelve species are unique to this arena (Allium regelianum, Salicornia borysthenica, Tulipa gesneriana). Chalbaska arena – forty-six rare species, of which six species are unique to this area (Ostericum palustre, Dactylorhiza majalis, Eremogone rigida). In fourth place is the Oleshkovska arena – forty-five species, ten rare are unique to this area (Carex atherodes, Epipactis palustris, Menyanthes trifoliata). Fifth place is occupied by the Zburyevska arena – thirty-two sozophytes, of which three species are characteristic only of it, namely: Athyrium felix-femina, Dryopteris filis-mas and Tephroseris palustris. Penultimate place is occupied by the Kozacho-Lagerska arena – twenty-six rare species of vascular plants, four sozophytes are characteristic only for this area, namely: Drosera rotundifolia, Nymphaea alna, N. candida and Schoenoplectus mucronatus. Last is Kakhovska arena – fifteen species and only one species is endemic – Doronicum hungaricum, but its location has not been established by the author.